A Relational Approach to Mentoring Women Doctoral Students. (September 2016) - Gammel, Jo Ann; Rutstein‐Riley, Amy
Abstract : Our study examines the relationships of six dyads of women advisors and advisees in one doctoral program to understand power, context, and personal transformation. We found that mentoring is context specific and power dynamics range from equitable to hierarchical. This article explores the connection between relational cultural theory and transformative learning.